2018
DOI: 10.1111/hsc.12588
|View full text |Cite
|
Sign up to set email alerts
|

A before and after study of integrated training sessions for children's health and care services

Abstract: Recent UK policy drivers such as the National Collaboration for Integrated Care and Support and Making Every Contact Count prioritise integrated care, an approach that seeks to provide more coordinated and seamless health and social care. In children's services, despite many partners, there are challenges around integrating care. A deprived borough of London ran short training and networking sessions for services supporting children and young people. This study examined whether intersectoral training would imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Social care as patching fragmentation of systems. Of the 33 initiatives selected, 3 aimed at improving fragmentation in health and social care systems (Bussu and Marshall, 2020;Murphy et al, 2017;Alexander et al, 2018). These included a service integration training package targeting clinicians' literacy around social services when conducting early interventions with children and their families (Alexander et al, 2018); an initiative that identified collaborative approaches and services for all sectors of society and age groups (Murphy et al, 2017) in the context of integrated care in the UK; and a novel system introducing care navigators who support complex adults and help them navigate the health and social care system (Bussu and Marshall, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social care as patching fragmentation of systems. Of the 33 initiatives selected, 3 aimed at improving fragmentation in health and social care systems (Bussu and Marshall, 2020;Murphy et al, 2017;Alexander et al, 2018). These included a service integration training package targeting clinicians' literacy around social services when conducting early interventions with children and their families (Alexander et al, 2018); an initiative that identified collaborative approaches and services for all sectors of society and age groups (Murphy et al, 2017) in the context of integrated care in the UK; and a novel system introducing care navigators who support complex adults and help them navigate the health and social care system (Bussu and Marshall, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 27 initiatives reporting having health and social care staff integrated in practice, with a strong role description and mapping, along with clear integrated governance (Aredes et al ., 2021; Terracciano et al ., 2021; Pruitt et al ., 2018; Cammy, 2017; Moretti, 2017; Bussu and Marshall, 2020; Perman et al ., 2021; Pauley et al ., 2016; Moon et al ., 2021; Mateo-Abad et al ., 2020; Eastwood et al ., 2020; Talbot et al ., 2020; Vestjens et al ., 2019; Spoorenberg et al ., 2019; Elston et al ., 2019; Ismail et al ., 2020; Wong et al ., 2020; Sadarangani et al ., 2019; Tong et al ., 2020; Doheny et al ., 2020; White et al ., 2021; Aboutanos et al ., 2019; Chng et al ., 2021; Janse et al ., 2016; Murphy et al ., 2017; Sohanpal et al ., 2017; Alexander et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RELEVANT STUDIES Scale up existing competencies among all practitioners to deliver more integrated care [15,30,13,36] Incorporate integrated care concepts organically, so that they are fundamental to delivering care Create a working environment that values wellness and creates a climate of respect and work-life balance [14,36] Engage faculty teaching staff who convey joy in their work and provide trainees with education around work-life balance, self-reflection and self-improvement [14] Embed structures to support collaboration and interprofessional learning among colleagues and professions across services, strengthening multisector relationships; multi-organisation training [33,47,48,11,36] Incorporate simulation-based scenarios using actors from the local community with lived experiences [49] Incorporate education and support for caregivers, including prevention of health problems and improving quality of life. For example, implement a weekly meeting for caregivers to discuss topics related to the experiences of the patients' healthcare and their self-care needs [37] Allow more time for networking, interprofessional education and opportunities for individual service presentations and diverse attendance, including the social care and voluntary sectors [47,50,36] Case studies, exercises and simulations are encouraged to allow students to interact with the content in as realistic a venue as possible [42] Focus on soft skills, such as communication, teamwork and relationship building [5,34,13,41] Focus on skills to build durable relationships with patients, other professionals and caregivers [5,34] Focus on self-management promotion and skills, including the use of motivational interviewing techniques [34] Skills to navigate the health and social care systems and work on individualised care plans and assessments [30,34,47,13] Ongoing mentorship [38,…”
Section: Modelmentioning
confidence: 99%
“…Facilitators included (1) high staff engagement (Chisholm et al 2019;Wills and Ion 2014), (2) the perception that staff are advocates for healthy lifestyles and initiating discussions (Keyworth et al 2019), (3) the professional-patient relationship to facilitate healthrelated discussions (Keyworth et al 2019;Wills and Ion 2014), and (4) incentives to create staff buy-in (Nelson et al 2013).…”
Section: (Iii) Staff Capacitymentioning
confidence: 99%